The main priority of achievement of resource safety of agricultural production - Pushak, Yaroslav; Orobchuk, Mykhailo; Marchenko, Olga (Research Papers in Economics and Finance, 2017)
Resource safety of agricultural production is investigated as the main condition. Its dominant registers are land resources and fertility of soil. The bearing-out of nutritives is analyzed from soil together with the harvest of agricultural cultures. It shall be underlined that for providing maintenance of areas and fertility, it is crucial to maintain a balance between the bearing-out of nutritives from soil with the harvest of agricultural cultures and compensative bringing. The major directions of maintenance of the resource providing agricultural production are the following: increase of bringing of organic fertilizers, optimization of the structure of croplands, strengthening the responsibility of land users, development of ecological culture.